2022
DOI: 10.1063/5.0103821
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of valley polarization in CVD grown monolayer MoS2 films

Abstract: The development of future valley based electronics or valleytronics requires a high degree of valley polarization (VP) in large area monolayer (1L)-MoS2. Though it is possible to synthesize 1L-MoS2 films with large area coverage, VP property of as-grown films is found to be very poor. Here, we investigate the role of physisorbed air molecules and strain on the luminescence and the VP characteristics of large area monolayer MoS2 grown on various substrates by a microcavity based chemical vapor deposition (CVD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…On the other hand, large area coverage and continuity of the 1L-MoS 2 films, which are essential to develop integrated electronics on this material platform, can be achieved by CVD technique [24,25]. However, CVD grown layers often suffer from imperfections, such as sulphur vacancies (V S ) [26][27][28][29][30], grain boundaries [31] and the residual strain [32,33], which deteriorate the electrical and optical performance of the material. Presence of sulphur vacancies makes these films more sensitive to the environmental conditions [34,35].…”
Section: K-valleysmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, large area coverage and continuity of the 1L-MoS 2 films, which are essential to develop integrated electronics on this material platform, can be achieved by CVD technique [24,25]. However, CVD grown layers often suffer from imperfections, such as sulphur vacancies (V S ) [26][27][28][29][30], grain boundaries [31] and the residual strain [32,33], which deteriorate the electrical and optical performance of the material. Presence of sulphur vacancies makes these films more sensitive to the environmental conditions [34,35].…”
Section: K-valleysmentioning
confidence: 99%
“…V S defects attached with air molecules are also responsible for the appearance of a broad luminescence band at low temperatures in CVD grown 1L-MoS 2 [30,32]. It has been found that upon vacuum annealing, the conductivity of the films improves by several orders of magnitude [29] and at the same time, defect luminescence is substantially suppressed [30,32]. Further, the valley polarization property of the films enhances quite significantly [30,32].…”
Section: K-valleysmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition-metal dichalcogenides (TMDCs), which are two-dimensional (2D)-layered semiconductors, have great potential for electronic and optoelectronic device applications. The class of materials exhibits several fascinating properties like large exciton binding energy; existence of many body bound states, e.g., trions and biexcitons; and thickness dependence of the electronic properties . Strong spin-valley coupling in monolayers also leads to the valley polarization effect, , which can be exploited to inject spin-polarized carriers and excitons for future spintronics and valleytronics. Due to their layered nature, lower dielectric constant, higher electron effective mass, and larger band gap than that of silicon, TMDCs are superior in suppressing the short channel effects that facilitate greater integration of devices in a chip.…”
Section: Introductionmentioning
confidence: 99%
“…Atomically thin transition metal dichalcogenides (TMDs), expected to be excellent candidate materials for photodetectors, electroluminescent devices, transistors and spintronics, have attracted extensive interests owing to its strong photoluminescence, remarkable mechanical strength and flexibility, atomic-scale thickness, and intriguing coupled spin-valley physics [1][2][3][4][5][6][7][8][9][10][11]. One distinctive feature of monolayer TMDs is the existence of a direct bandgap.…”
Section: Introductionmentioning
confidence: 99%